THE STUDENTS’ ATTITUDES IN ONLINE CROSS CULTURE UNDERSTANDING CLASS : THE STUDENTS’ ATTITUDES IN ONLINE CROSS CULTURE UNDERSTANDING CLASS - Vitasmoro, Pamadya; Darodjat, Tubagus Achmad; Suasungnern, Sineerat; Jatmiko, Jatmiko (International Journal of Performing Arts (IJPA), 2024)
Online teaching is a way of teaching that integrates some technology to teach long-distance and it is facilitated with application and internet access. This research focuses on the student’s attitudes in online cross-culture understanding classes. There are some procedures the researcher takes to collect the data, such as: preparing the questionnaire for the students to answer. The questionnaire is based on the data needed for describing the students’ attitudes. Then the researcher distributed the questionnaire to each student through the WA group and email. After all the questionnaire is submitted then analyzed. The place for research is in an online cross-culture class at the University of Nusantara PGRI Kediri. This subject is taught in the seventh semester of the academic year 2020-2021.